PELATIHAN DIGITAL MARKETING BERBASIS POTENSI LOKAL DAERAH PADA ANGGOTA KARANG TARUNA DESA WANGEN KABUPATEN KLATEN - Puspa Novita Sari (Universitas Muhammadiyah Mataram, 2023)
ABSTRAKPemanfaatan teknologi informasi dan komunikasi di era digital yang semakin berkembang telah menjadi kebutuhan bagi setiap individu, organisasi, maupun komunitas. Hal ini seiring dengan perubahan perilaku masyarakat dalam mengakses informasi. Desa Wangen merupakan salah satu desa di Kecamatan Polanharjo, Kabupaten Klaten, yang kaya akan potensi di sektor pertanian, pariwisata, kerajinan tangan, dan UMKM. Namun, masih terdapat kendala dalam memasarkan produk-produk tersebut secara efektif. Kendala tersebut dihadapi oleh anggota Karang Taruna Desa Wangen. Desa Wangen memiliki beragam produk unggulan yang dapat dikembangkan melalui pemasaran digital, namun masih minim pengetahuan dan keterampilan dalam hal tersebut. Tujuan kegiatan pengabdian masyarakat ini adalah memberikan pengetahuan dan wawasan terkait digital marketing untuk mengembangkan potensi lokal. Metode pelaksanaan diselenggarakan dalam 3 (tiga) tahapan pelaksanaan yakni focus group discussion, sarasehan, dan pendampingan teknis. Hasil pengabdian adalah peserta pelatihan mampu memanfaatkan digital marketing untuk memasarkan produk yang tercermin dalam business project. Kata kunci: pemasaran digital; pelatihan; potensi lokal; kewirausahaan; karang taruna. ABSTRACTThe use of information and communication technology in the growing digital era has become a necessity for every individual, organization, and community. This is in line with the changes in people's behavior in accessing information. Wangen Village is one of the villages in Polanharjo Sub-district, Klaten Regency, which is rich in potential in the agricultural, tourism, handicraft, and MSME sectors. However, there are still obstacles in effectively marketing these products. These obstacles are faced by the members of Karang Taruna in Wangen Village. Wangen Village has various superior products that can be developed through digital marketing, but still lacks knowledge and skills in this regard. Therefore, digital marketing training can be a solution to the problem of equipping Karang Taruna members in developing local potential. The training is held in three stages, namely focus group discussions, seminars, and technical assistance. The output of the activity is a business project created by the participants, where the majority of 45% of the entire group chose the culinary sector. Overall, the value of each training dimension ranges from 4.01 to 5.00, and the average value of all training dimensions is 4.27 or if expressed in percentage, the success rate is 85.4%. This indicates that, viewed from the dimensions of goals and objectives, material, instructors, methods, and participants, the implementation of the training program can be considered successful. Keywords: digital marketing; training; local potential; entrepreneurship; youth organization